Approximate Solutions of the One-Dimensional Fisher–Kolmogorov–Petrovskii– Piskunov Equation with Quasilocal Competitive Losses; Russian Physics Journal; Vol. 60, iss. 9 - Shapovalov A. V. Aleksandr Vasilyevich (2018, 2018)
Title screen